Imidacloprid-mediated stress on non-Bt and Bt cotton, aphid and ladybug interaction: Approaches based on insect behaviour, fluorescence, dark respiration and plant electrophysiology - Pachú, Jéssica K.S.; Macedo, Francynes C.O.; da Silva, Fábia B.; Malaquias, José B. [UNESP]; Ramalho, Francisco S.; Oliveira, Ricardo F.; Godoy, Wesley A.C. (Elsevier, 2021)
Plants and insects are parts of a complex system that involves interactions among many trophic levels, and it is important to understand the nature of such interactions. In the complex of interactions involving aphids and transgenic cotton expressing Bacillus thuringiensis, both the spraying of neonicotinoids and the occurrence of predatory coccinellids are common. However, there are gaps regarding the knowledge about possible impacts of neonicotinoids on physiological variables of the host plant and behavioural traits of the aphid (Aphis gossypii) and predator (Cycloneda sanguinea). Therefore, this study aimed to highlight the photosynthetic and electrical responses of the plant to the stress caused by the aphid attack combined with the stress generated by the use of imidacloprid in Bt and non-Bt cotton (Gossypium hirsutum L.) cultivars and to evaluate how this stress can influence the behavioural ecology of the predator and prey. Chlorophyll a fluorescence tests, dark respiration and electrophysiology on non-Bt and Bt cotton were carried out, the behaviour of the prey and predator was also evaluated with a video capture system. Our research is a study model that generates insights about possible impacts when using Imidacloprid without the occurrence of the pest on the plant, because the exposure of non-Bt and Bt cotton plants and the predator to imidacloprid unnecessarily, may result in stress on the physiology of the cotton plants and on the behaviour of the predator.
Keywords: Impact; Neonicotinoid; Plant physiology; Predator behaviour